2013
DOI: 10.1589/jpts.25.173
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammation Effects of Low Intensity Laser Therapy on Monosodium Iodoacetate-induced Osteoarthritis in Rats

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effects of low intensity laser therapy (LILT) on inflammatory osteoarthritis in the knee joint of rats.[Subjects] Thirty Sprague-Dawley rats were randomly divided into 3 groups with 10 rats each: the normal, control, and LILT groups. The arthritis group was treated with LILT using a gallium-aluminum-arsenide diode laser over during 3 weeks. All treatments were applied once a day, 5 days per week for 21 days. The inflammation cytokine and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…37 Kim and Kim conducted a 3-week treatment using an 850 nm galliumaluminum-arsenide laser, resulting in the weight-bearing difference, PWMT, and PWL significantly reversed, and the serum levels of TNF-a, IL-1b, and IL-6 also decreased in a MIA-induced KOA model. 29 These results indicated that different parameters of laser intervention have differ-ent effects on MIA-induced KOA pain. Future studies should compare the parameters of laser, determining the optimal treatment parameters, producing long-lasting analgesic effects, and more importantly, reducing or replacing the use of drugs.…”
Section: Effects Of Laser Moxibustion On Mia-induced Koamentioning
confidence: 86%
See 1 more Smart Citation
“…37 Kim and Kim conducted a 3-week treatment using an 850 nm galliumaluminum-arsenide laser, resulting in the weight-bearing difference, PWMT, and PWL significantly reversed, and the serum levels of TNF-a, IL-1b, and IL-6 also decreased in a MIA-induced KOA model. 29 These results indicated that different parameters of laser intervention have differ-ent effects on MIA-induced KOA pain. Future studies should compare the parameters of laser, determining the optimal treatment parameters, producing long-lasting analgesic effects, and more importantly, reducing or replacing the use of drugs.…”
Section: Effects Of Laser Moxibustion On Mia-induced Koamentioning
confidence: 86%
“…found that a low-intensity laser can inhibit inflammatory cell infiltration, reduce the expression of proinflammatory cytokines and produce antinociceptive effects. 29 Histopathology showed that a low-intensity laser could alleviate synovitis, cartilage injury, and subchondral bone destruction, which may have a certain cartilage protection effect. 30 However, most of the currently used low-intensity lasers are semiconductor lasers, and more importantly, they only have the effect of a ''light needle'' due to their limited thermal effects.…”
Section: Effects Of Laser Moxibustion On Mia-induced Koamentioning
confidence: 99%
“…In literature, different results are reported about the K-L grade and response to PRP treatment in knee osteoarthritis. [3,[23][24][25] However, today the prominent opinion is that PRP responses are better in low K-L grade patients with little joint and cartilage degeneration. [1,3,5] Factors such as the reduction of living cells and the anabolic response to growth factors, the loss of chondrocytes, the thinning of the cartilage plate, deficient muscular functions and joint instability due to increased ligament laxity could reduce the effectiveness of PRP as joint degeneration increases.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[23][24][25] However, today the prominent opinion is that PRP responses are better in low K-L grade patients with little joint and cartilage degeneration. [1,3,5] Factors such as the reduction of living cells and the anabolic response to growth factors, the loss of chondrocytes, the thinning of the cartilage plate, deficient muscular functions and joint instability due to increased ligament laxity could reduce the effectiveness of PRP as joint degeneration increases. [1,12] It is believed that PRP might not have any direct effect on the anabolic process in chondrocytes in the advanced stages of OA but that it may have an anti-inflammatory effect through the regulation of common homeostasis and cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation